1995
DOI: 10.1097/00001888-199507000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medical school curricula, faculty role models, and biomedical research support on choice of generalist physician careers

Abstract: The authors evaluated and reviewed the literature on the effects of medical school curricula, faculty role models, and federal biomedical research support on the specialty choices of U.S. medical students. All 275 articles on these subjects published from 1984 through 1993 were considered. An instrument was developed to assess the quality of the articles. A total of 85 articles met study criteria and were reviewed. The mean score achieved was 42.7% of the total possible points. Major educational reforms emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
10

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 0 publications
5
49
0
10
Order By: Relevance
“…7,8 However, while individual factors may be the most powerful influences, studies have indicated that certain experiences during training can complement these inherent characteristics regarding career choices. [9][10][11][12][13] In assessing the pre-existing characteristics of our study cohort, we found that participants not only had a great deal of non-academic international experience prior to residency, they chose Yale for training in part because of its international elective program. Moreover, residents stated that cross-cultural experience and a desire to serve a less privileged population were the most important, not the most frequent, reasons for participation.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, while individual factors may be the most powerful influences, studies have indicated that certain experiences during training can complement these inherent characteristics regarding career choices. [9][10][11][12][13] In assessing the pre-existing characteristics of our study cohort, we found that participants not only had a great deal of non-academic international experience prior to residency, they chose Yale for training in part because of its international elective program. Moreover, residents stated that cross-cultural experience and a desire to serve a less privileged population were the most important, not the most frequent, reasons for participation.…”
Section: Discussionmentioning
confidence: 99%
“…Three other literature reviews have examined primary care specialty choice and have reached similar conclusions (Appendix 1), [11][12][13] but were also limited to North American studies. Since Bland and colleagues' comprehensive review, medical schools around the world have developed new initiatives in recognition of the need to increase students' exposure to primary care.…”
Section: Introductionmentioning
confidence: 90%
“…Bland et al 9 and Meurer 10 covered most factors related to specialty choice. The review by Campos-Outcalt et al 11 was limited to just 3 areas, curricula, role models and school funding. 10 The conclusions of these 3 reviews, which included research published through 1993, serve as the starting point for this one, which critically reviews the literature published since 1993 on the choice of family medicine as a specialty.…”
mentioning
confidence: 99%